"Exploring Strategy. Text and Cases" - Fernández Portillo, Luis (Revista de Fomento Social, 2015)
Reseña de la obra de: JOHNSON, G., WHITTINGTON, R.; SCHOLES, K.; ANGWIN, D.; REGNÉR, P. (2014), Exploring Strategy. Text and Cases (10th Edition), Harlow, Pearson, 783 pp.